Adiposity and carotid-intima media thickness in children and adolescents: a systematic review. Issue 1 (December 2015) - Park, Min; Skow, Áine; De Matteis, Sara; Kessel, Anthony; Saxena, Sonia; Viner, Russell; Kinra, Sanjay
Abstract Background Adiposity in childhood is associated with later cardiovascular disease (CVD), but it is unclear whether this relationship is independent of other risk factors experienced in later life, such as smoking and hypertension. Carotid-intima media thickness (cIMT) is a measure of subclinical atherosclerosis that may be used to assess CVD risk in young people. The aim of this study was to examine the relationship between adiposity and cIMT in children and adolescents. Methods We searched Medline, Embase, Global Health, and CINAHL Plus electronic databases (1980–2014). Population-based observational studies that reported a measure of association between objectively-measured adiposity and cIMT in childhood were included in this review. Results Twenty-two cross-sectional studies were included (n = 7, 366 children and adolescents). Thirteen of nineteen studies conducted in adolescent populations (mean age ≥12 years, n = 5, 986) reported positive associations between cIMT and adiposity measures (correlation coefficients 0.13 to 0.59). Three studies of pre-adolescent populations (n = 1, 380) reported mixed evidence, two studies finding no evidence of a correlation, and one an inverse relationship between skinfolds and cIMT. Included studies did not report an adiposity threshold for subclinical atherosclerosis. Conclusions Based on studies conducted mostly in Western Europe and the US, adiposity does not appear to be associated with cIMT in pre-adolescents, but may be associated in adolescents. If further studies confirm these findings, a focus on cardiovascular disease prevention efforts in pre-adolescence, before arterial changes have emerged, may be justified.